The Inclusion of Children on the Autism Spectrum in the Design of Learning Technologies: A Small-Scale Exploration of Adults’ Perspectives - Boyle, Bryan; Arnedillo-Sanchez, Inmaculada (Frontiers in Education, 2022)
This research explores the inclusion of children on the autism spectrum in the design of educational technology from the perspectives of adult co-designers. A group of five non-verbal children with a diagnosis of autism participated in a series of four design workshops over the course of six weeks. Using a participatory design approach, a small team of three teachers and two technology developers worked alongside the children to design a language development and literacy app for use in a special education classroom. The outcome of this process was a stand-alone education app that comprised many of the contributions made by children during the workshops. The inclusion of children with autism in technology design ensures the end-product reflects their education needs and requirements. Using a qualitative approach, this small-scale study sought to examine the participation of children with autism through the various stages of the design process from the perspectives of their teachers and technology designers. Data were collected through individual interviews and a focus group with teachers and technology designers. Three major themes emerged from thematic analysis: 1) valuing contribution; 2) the challenge of listening; and 3) ownership in outcome. Emerging subthemes highlight challenges described by teachers and designers in facilitating and maintaining meaningful participation in design activities and their efforts to address these. Findings emphasise the value of participation while questioning participatory practices for specific phases of design. The study explores the challenges of equalising power between adults and children with autism in participatory design projects. It uncovers tension between the desire to ensure the authentic participation of children with autism where communication and engagement is significantly compromised by the complexity of their disability. The small number of participants and the modest scope of this design project limit the generalisability of the findings. However, it points to the value of recognising children’s contributions and the importance of striving to incorporate these in the final design artefact.